HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN PUNGGUNG DENGAN KETEPATAN JUMPING SMASH ATLET REMAJA PUTRA PB.FORT DE KOCK BUKITTINGGI - Salfet Ali Sidiq; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This problem aims to prove whether the correlation between power of legs and back flexibility with jumping smash accuracy teenager athlete of Badminton Club Fort De Kock Bukittinggi. The forms of this research are the correlation study, the population in this study from the teenager athlete of Badminton Club Fort De Kock Bukittinggi, and the sample in this study is the teenager athlete of Badminton Club Fort De Kock Bukittinggi which have numbered 9 athlete. The first power of legs (X1) with jumping smash accuracy (Y), where rtable at significant level α 0,05) = 0,707 means rresult (0,83) > rtable (0,707), which means the hypothesis is accepted and there is a meaningful correlation between power of legs with jumping smash accuracy teenager athlete of Badminton Club Fort De Kock Bukittinggi, a secound analysis of in the calculation of the correlation between X2 and Y, where rtable at significant level a (0,05) = 0,707 means rresult (0,739) > rtable (0,707), which means the hypothesis is accepted and there is a meaningful back flexibility with jumping smash accuracy teenager athlete of Badminton Club Fort De Kock Bukittinggi. the analysis of the three correlation power of legs (X1) and back flexibility (X2) jumping smash accuracy (Y) was ontained, which rtable at significant level α (0,05) = 0,707, means rresult (0,828) > rtable (0,707). Then it can be concluded that the correlation between (X1) and (X2) with results (Y) or the correlation between power of legs and back flexibility with jumping smash accuracy are significant. There fore the jumping smash accuracy teenager athlete of Badminton Club Fort De Kock Bukittinggi in the fore cast with their power and flexibility.Key Words: power, flexibility, jumping smash